Magnetoelectric CoFe2O4/polyvinylidene fluoride electrospun nanofibres - Gonçalves, R. (2015)
Magnetoelectric 0-1 composites comprising CoFe2O4 (CFO) nanoparticles in polyvinylidene fluoride (PVDF) polymerfibre matrix have been prepared by electrospinning. The average diameter of the electrospun composite fibres D is ~ 325 nm, independently of nanoparticle content, and the amount of crystalline polar β phase is strongly enhanced when compared to pure PVDF polymer fibres. The piezoelectric response of these electroactive nanofibres is modified by an applied magnetic field, thus evidencing the magnetoelectric character of the CFO/PVDF 0-1 composites.